1989
DOI: 10.1259/0007-1285-62-736-326
|View full text |Cite
|
Sign up to set email alerts
|

Acute rhabdomyolysis: evaluation with magnetic resonance imaging compared with computed tomography and ultrasonography

Abstract: Fifteen patients with acute rhabdomyolysis were evaluated with low field magnetic resonance (MR) imaging and the results compared with those obtained using computed tomography (CT) and ultrasonography (US). With MR imaging, abnormal muscles with areas of increased signal intensity were seen in every patient, which probably reflects increased water content or increased mobility of water molecules caused by inflammatory reaction and oedema in the injured and necrotic muscles. Computed tomography without intraven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
42
0
6

Year Published

1999
1999
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(50 citation statements)
references
References 20 publications
2
42
0
6
Order By: Relevance
“…3 More recently, Jain et al reported low density of the lateral pterygoid muscles on CT with subsequent hyperintensity and contrast enhancement on MRI done several days later in a 28-year-old with psychiatric problems who was admitted to the hospital for an acetaminophen overdose. 4 CT and MRI findings of rhabdomyolysis in the extremities have also been reported, 9,10 and two types of rhabdomyolysis have been described. 9 Type I rhabdomyolysis presents with oedema and the affected muscles reveal homogeneous isointensity to hypointensity on T 1 -weighted images, homogeneous hyperintensity on T 2 -weighted and STIR images and homogeneous enhancement.…”
Section: Discussionmentioning
confidence: 95%
“…3 More recently, Jain et al reported low density of the lateral pterygoid muscles on CT with subsequent hyperintensity and contrast enhancement on MRI done several days later in a 28-year-old with psychiatric problems who was admitted to the hospital for an acetaminophen overdose. 4 CT and MRI findings of rhabdomyolysis in the extremities have also been reported, 9,10 and two types of rhabdomyolysis have been described. 9 Type I rhabdomyolysis presents with oedema and the affected muscles reveal homogeneous isointensity to hypointensity on T 1 -weighted images, homogeneous hyperintensity on T 2 -weighted and STIR images and homogeneous enhancement.…”
Section: Discussionmentioning
confidence: 95%
“…Review of medical records has shown that MR images can be used to effectively localise muscle lesions in rhabdomyolysis and assess extent [4,[7][8][9][10][11][12]. MRI has been shown to be more sensitive for detection of rhabdomyolysis skeletal muscle lesions than ultrasonography and CT [8].…”
mentioning
confidence: 99%
“…However, these are nonspecific imaging findings that can also be seen in pyomyositis and infiltrative intramuscular neoplasms. (7,10,11) On ultrasonography, affected muscle groups generally appear hypoechoic, with effacement of the normal striated architecture of the muscle fibres, although these findings are also nonspecific. (11,12) In the absence of relevant clinical history and laboratory markers, radiological findings of rhabdomyolysis may be difficult to distinguish from those of inflammatory myopathy, muscle infection, necrotising fasciitis or other conditions associated with myonecrosis such as diabetes mellitus or sickle cell crisis.…”
Section: Discussionmentioning
confidence: 99%